العوامل المؤدية إلى التحرش الجنسي بالمرأة في المجتمع الجزائري - ابريعم, سامية (Changement Social, 2018)
معرفة  العوامل المؤدية إلى التحرش الجنسي بالمرأة في المجتمع الجزائري من وجهة نظر عينة من الطالبات في جامعة أم البواقي. وقد اعتمدت الدراسة على المنهج الوصفي التحليلي، حيث قامت الباحثة بتطبيق مقياس العوامل المؤدية إلى التحرش الجنسي بالمرأة من إعداد (محمود فتحي محمد)، على عينة تتكون من (140) طالبة من طالبات جامعة أم البواقي، وقد توصلت الدراسة إلى أن: - أهم العوامل المؤدية إلى التحرش الجنسي  بالمرأة في المجتمع الجزائري من وجهة نظر عينة من طالبات جامعة أم البواقي هي على الترتيب: العوامل الإعلامية، ثم العوامل الشخصية،ثم العوامل الأسرية، يليها العوامل الاقتصادية، فالعوامل الدينية. The current study aimed at identifying the factors that lead to sexual harassment of women in Algerian society from the point of view of a sample of female students at the Oum El Bouaghi university. The study was based on a descriptive analytical approach. The researcher applied a Scale on the factors leading to sexual harassment of women by (Mahmoud Fathi Mohammed) on a sample of 140 female students from the Oum El Bouaghi university.The study concluded that: - The most important factors leading to sexual harassment of women in Algerian society from the point of view of a sample of female students of Oum El Bouaghi university are respectively:Media factors, personal factors, family factors, economic factors, and religious factors.